2020
DOI: 10.3399/bjgp20x708149
|View full text |Cite
|
Sign up to set email alerts
|

How primary care can help survivors of transient ischaemic attack and stroke return to work: focus groups with stakeholders from a UK community

Abstract: BackgroundEvidence about how primary care can best enable survivors of transient ischaemic attack (TIA)/stroke return to work is limited.AimThis study explored the role of primary care in supporting survivors of transient ischaemic attack (TIA)/stroke return to work with stakeholders from a local UK community.DesignA qualitative study using framework analysis.MethodFour focus groups were carried out in Cambridgeshire, UK, between September and November 2015. The 18 participants included survivors of TIA/stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Majority of the studies ( n = 22) included nursing staff. Some studies also examined the experiences of patients and their carers (Balasooriya‐Smeekens et al, 2020; Bright et al, 2018; Chuenjairuang et al, 2012; Harrison et al, 2017; O'Halloran et al, 2010; Sadler et al, 2017; Turner et al, 2019). The total number of participants in the studies varied between 8–806.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of the studies ( n = 22) included nursing staff. Some studies also examined the experiences of patients and their carers (Balasooriya‐Smeekens et al, 2020; Bright et al, 2018; Chuenjairuang et al, 2012; Harrison et al, 2017; O'Halloran et al, 2010; Sadler et al, 2017; Turner et al, 2019). The total number of participants in the studies varied between 8–806.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, specialist knowledge in stroke teams (Burau et al, 2017; Longley et al, 2018) and networks spanning localities (Christiansen et al, 2017) were felt to reinforce interprofessional collaboration and advance competence in providing high‐quality needs‐based care. However, participants in several studies also felt that the quality of care and rehabilitation were undermined by organisational factors (Lam et al, 2016; Loft et al, 2017; Ryan et al, 2017) such as inadequate or variable resources (time, staff capacity, physical environment) in different phases of the care path (Balasooriya‐Smeekens et al, 2020; Harrison et al, 2017) and pressure to discharge patients early (Kable et al, 2019; Luker et al, 2014). Harrison et al (2017) found that a lack of specific resources such as psychological expertise caused frustration among healthcare professionals and led to an emphasis on medicating patients during care.…”
Section: Resultsmentioning
confidence: 99%
“…A recent exploratory review of secondary preventative measures for people with TIA suggests that many of this population have unmet needs and that current assessment tools lack the appropriate sensitivity to identify subtle impairment 39. Evidence highlights a mismatch between patient needs and services provided for the individual with TIA or mild stroke,40 with motivated participants unable to access the support they felt necessary to help them make changes to lifestyle behaviors 31. It is probable that, for participants of our study, the perception of invisibility associated with TIA, an absence of physical impairment, and a lack of targeted information may have perpetuated the belief that their stroke posed no threat 41…”
Section: Discussionmentioning
confidence: 99%
“…For example, fatigue has been reported as a factor associated with reduced return-to-work rates in 4 quantitative studies, 19,47,80,102 and also as a barrier impeding return to work in 16 qualitative studies, evaluations, or patient information leaflets. [21][22][23][24]46,51,52,62,118,[121][122][123][124][125][126]128,129 Barriers were grouped and ranked within each group according to the number of sources in which they were mentioned (Table 4). For person-related barriers, cognitive impairments and fatigue were most frequently reported.…”
Section: Barriers and Facilitatorsmentioning
confidence: 99%
“…45 Finally, barriers and facilitators related to the employer were identified, such as (lack of) support 41,43 ; (lack of) accommodation for the person's needs [41][42][43]45 ; and legislation to support people with disabilities. 43 In addition, there were 23 primary research studies, [21][22][23][24][25][60][61][62][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129] 1 service evaluation, 46 1 report from a symposium, 47 3 guidelines, 48-50 4 patient information leaflets, 51-54 and 1 magazine article 55 that reported barriers and facilitators. For these 33 records, and following the approach taken in the systematic review by Schwarz et al, 29 barriers and facilitators were categorized by whether they related to the person, rehabilitation services, or the employer, or to the interactions between these 3 stakeholders, and then ranked within these groups.…”
Section: Barriers and Facilitatorsmentioning
confidence: 99%